Pediatric reference intervals for 28 chemistries and immunoassays on the Roche cobas (R) 6000 analyzer-A CALIPER pilot study - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
Objective: The aim of this study was to determine age- and sex-specific pediatric reference intervals for 28 analytes on the Roche cobas (R) 6000 analyzer. Design and methods: The study was conducted at the Hospital for Sick Children in Toronto, Canada. Approximately 600 outpatient samples from a pediatric population deemed to be metabolically stable were subdivided into five age classes ranging from 0 to 20 years of age and further partitioned by gender. Reference intervals were established, after removal of samples significantly affected by hemolysis, icterus and lipemia and outlier exclusion, using the Robust statistical method to obtain the 2.5th and 97.5th percentiles. Results: Age (birth to 20 years of age) and gender-appropriate pediatric reference intervals for 28 analytes are reported. Conclusions: These reference intervals provide the basis for clinical interpretation of laboratory results using the Roche cobas (R) 6000 analyzer or related instrumentation/methods, provided adequate reference interval verification studies are performed. (C) 2010 The Canadian Society of Clinical Chemists. Published by Elsevier Inc. All rights reserved.
Keywords: Reference intervals; Pediatric; CALIPER; Biochemistry; GAP ANALYSIS; GROWTH-HORMONE; INSULIN; ROBUST; SYSTEM